Music theory and natural order: From the renaissance to the early twentieth century - Clark, Suzannah; Rehding, Alexander (Cambridge Cambridge University Press, 2001)
Music theorists of almost all ages employ a concept of "Nature" to justify observations or statements about music. The understanding of what "Nature" is, however, is subject to cultural and historical differences. In tracing these explanatory strategies and their changes in music theories between c. 1600 and 1900, these essays explore (for the first time in a book-length study) how the multifarious conceptions of nature, located variously between scientific reason and divine power, are brought to bear on music theory and how they affect our understanding of music.